ANALISIS PENGENDALIAN KUALITAS PRODUK NATA DE COCO DENGAN METODE SIX SIGMA DI CV XYZ - Muhammad Arif; Ari Zaqi Al Faritsy (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the quality control of 0.3 cm cut nata de coco products at CV XYZ using the Six sigma method. Based on the results of the study, it is known that in the production process of 0.3 cm cut nata de coco, there are 2 types of defective products, namely shaved nata and frog nata. This sample data was taken in the production on internal machine 2. To overcome this problem, the appropriate method is the Six sigma method. The stages of Six sigma include Define, Measure, Analyze, Improve, and Control (DMAIC). The results of this study indicate several main factors causing defective products in 0.3 cm cut nata de coco are lack of training and high workload, not carrying out regular machine maintenance, no written SOP, no quality standards, no thickness measuring tools available, and an uncomfortable environment. This study successfully provided suggestions for improvements to reduce the level of defective products, namely morning briefing, making written SOP, emphasizing good quality standards, providing measuring instruments, and providing Earplugs to employees who operate noisy machines. Recommendation for improvements are expected to improve the quality of 0.3 cut nata de coco production at CV XYZ.